Quality of life in adults with sickle cell disease: an integrative review of the literature - Sandra Luzinete Felix de Freitas; Maria Lucia Ivo; Maria Stella Figueiredo; Maria Auxiliadora de Souza Gerk; Cristina Brandt Nunes; Fernando de Freitas Monteiro
ABSTRACT Objective: To identify the available evidence in the literature on health-related quality of life in adults with sickle cell disease. Method: integrative review of MEDLINE, CUMED, LILACS and SciELO databases, from articles developed in this area, published between 2005 and 2015, in English, Portuguese or Spanish. Results: 22 articles were included, six scales were used to evaluate health-related quality of life scores: three generic and three specific. No specific scale for adults with sickle cell disease has been adapted to Brazilian Portuguese so far. Patients affected by frequent painful crises, with low adherence to treatment, had a compromised quality of life. Conclusion: Selected studies have shown that patients with sickle cell disease have worse scores than the general population. These indicators should be instrumental to the nurse in the proposal of interventions and strategies of assistance and socio-educational, with a view to improving the quality of life of this clientele.